Translation Practices of Kalandraka and oqo Publishers and their Multilocal Dynamics: Two Cases of Pride, Profit and Success in Galicia. - Sánchez Moreiras, Miriam (Galicia 21: Journal of Contemporary Galician Studies, 2019)
The launch of the publisher Kalandraka in 1998, with its innovative proposal of producing its own children's picture books, followed by oqo in 2005 from an internal split of the company, was a salutary lesson in the Galician publishing market for children's literature. In addition to the excellence of their products, recognized inside and outside of the Iberian Peninsula, both publishers are characterized by the multilingual and international commitment of their respective projects. After pointing, in a general way, to the reasons for their success in the global market with the glocal dynamics that govern it, this article will focus on the particularities of the translation practices developed by Kalandraka and oqo and the features that stand out from the rest of the Galician publishing industry. The analysis will be based on the theoretical framework provided by the notions of pride and profit, as formulated by Heller and Duchêne (2012) from the field of Sociolinguistics, and by the notions of multi-local and cosmopolitan localism proposed by Manzini (2003, 2013) from the field of Sustainable Design. Its ultimate purpose is to consider the possibility and viability of sustainable models in the Galician publishing translation practices.